Using E. coli-based cell-free protein synthesis to evaluate the kinetic performance of an orthogonal tRNA and aminoacyl-tRNA synthetase pair - ALBAYRAK, CEM; Albayrak, CEM; Swartz, James R. (My University, 2013)
Even though the orthogonal tRNA and aminoacyl-tRNA synthetase pairs derived from the archaeon Methanocaldococcus jannaschii have been used for many years for site-specific incorporation of non-natural amino acids (nnAAs) in Escherichia coli, their kinetic parameters have not been evaluated. Here we use a cell-free protein synthesis (CFPS) system to control the concentrations of the orthogonal components in order to evaluate their performance while supporting synthesis of modified proteins (i.e. proteins with nnAAs). Titration experiments and estimates of turnover numbers suggest that the orthogonal synthetase is a very slow catalyst when compared to the native E. coli synthetases. The estimated kat for the orthogonal synthetase specific to the nnAA p-propargyloxyphenylalanine (pPaF) is 5.4 x 10(-5) s(-1). Thus, this catalyst may be the limiting factor for nnAA incorporation when using this approach. These titration experiments also resulted in the highest reported cell-free accumulation of two different modified proteins (450 +/- 20 mu g/ml CAT109pAzF and 428 +/- 2 mu g/ml sfGFP23pPaF) using the standard KC6 cell extract and either the PANOx SP or the inexpensive Glu NMP cell-free recipe. (C) 2012 Elsevier Inc. All rights reserved.